2017
DOI: 10.1172/jci95995
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylguanidino valeric acid is a marker of liver fat and predicts diabetes

Abstract: Unbiased, "nontargeted" metabolite profiling techniques hold considerable promise for biomarker and pathway discovery, in spite of the lack of successful applications to human disease. By integrating nontargeted metabolomics, genetics, and detailed human phenotyping, we identified dimethylguanidino valeric acid (DMGV) as an independent biomarker of CTdefined nonalcoholic fatty liver disease (NAFLD) in the offspring cohort of the Framingham Heart Study (FHS) participants. We verified the relationship between DM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
98
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 43 publications
7
98
1
Order By: Relevance
“…An elegant study was reported containing several large clinical cohorts containing biopsy-proven NASH patients that also had liver fat determined by CT. Serum metabolomics identified the top metabolite associated with liver fat as a mass of 202.1185 + . Databases contained a large number of hits for this mass and so a GWAS strategy was adopted yielding SNPs for the AGXT2 gene whose expressed enzyme produces a metabolite, dimethylguanidino valeric acid (DMGV), which matched this mass [191]. In terms of a biomarker for NASH or NAFL, DMGV displayed a wide overlap between control and NASH with approx.…”
Section: Nafl and Nashmentioning
confidence: 99%
“…An elegant study was reported containing several large clinical cohorts containing biopsy-proven NASH patients that also had liver fat determined by CT. Serum metabolomics identified the top metabolite associated with liver fat as a mass of 202.1185 + . Databases contained a large number of hits for this mass and so a GWAS strategy was adopted yielding SNPs for the AGXT2 gene whose expressed enzyme produces a metabolite, dimethylguanidino valeric acid (DMGV), which matched this mass [191]. In terms of a biomarker for NASH or NAFL, DMGV displayed a wide overlap between control and NASH with approx.…”
Section: Nafl and Nashmentioning
confidence: 99%
“…Urea cycle metabolites (arginine, citrulline, ornithine), and methylarginines (ADMA, SDMA, NMMA) were analysed using a targeted approach (Broad Institute). Raw data were obtained and processed using liquid chromatography tandem mass spectrometry, as previously described . The coefficient of variation for each metabolite was: arginine, 2.5%; ornithine, 2.4%; citrulline, 2.1%; ADMA, 7.2%; SDMA, 4.5%; NMMA, 5.5%.…”
Section: Methodsmentioning
confidence: 99%
“…Raw data were obtained and processed using liquid chromatography tandem mass spectrometry, as previously described. 5 The coefficient of variation for each metabolite was: arginine, 2.5%; ornithine, 2.4%; citrulline, 2.1%; ADMA, 7.2%; SDMA, 4.5%; NMMA, 5.5%.…”
Section: Blood Specimens and Metabolite Profilingmentioning
confidence: 95%
“…These approaches developed by bioinformaticians utilize modern computational developments in network analytics and machine learning algorithms and have the potential to uncover biological networks and association that may not have been identifiable using traditional candidate approaches . O'Sullivan et al have demonstrated the integration of nontargeted metabolomics, genetics, and detailed human phenotyping in biomarker discovery. Using this approach, they identified dimethylguanidino valeric acid as an independent biomarker of nonalcoholic fatty liver disease in the offspring cohort of the Framingham Heart Study …”
Section: Unbiased “Omics” Approachesmentioning
confidence: 99%
“…O'Sullivan et al have demonstrated the integration of nontargeted metabolomics, genetics, and detailed human phenotyping in biomarker discovery. Using this approach, they identified dimethylguanidino valeric acid as an independent biomarker of nonalcoholic fatty liver disease in the offspring cohort of the Framingham Heart Study …”
Section: Unbiased “Omics” Approachesmentioning
confidence: 99%